SOCIAL ADAPTATION OF ADOLESCENTS (Medical science of Uzbekistan, 2023)
The purpose of the work was to study the state of vegetative stability and social adaptation in adolescents 14–15 years old living in an industrial city and rural areas. The lowest rates of social adaptation were observed among urban schoolgirls compared to rural ones. The highest rates of social adaptation were recorded among rural schoolchildren. The lowest rates of vegetative stability were found in male gymnasium students. However, the highest rates of vegetative resistance were obseved among schoolgirls living in rural areas. Adolescents with low levels of vegetative stability and social adaptation should undergo additional examination and depending on its results, receive a rehabilitation course with the participation of a doctor, psychologist and teacher.